Social emotional well-being: What we do and its impact on development? - A literature review - Devi Risma; Hendriati Agustiani; Aulia Iskandarsyah; Ratna Jatnika (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
Social-Emotional Well-Being (SEWB) is an integral part of a child's development that affects learning readiness, academic success, and long-term psychological well-being. This article examines the impact of SEWB on child development and the approaches that can be taken to improve it, especially in early childhood. The method used was a systematic literature review of articles published between 2010 and 2023, focusing on early childhood SEWB. The technique used was a systematic literature review of 11 articles published between 2010 and 2023, focusing on early childhood SEWB. The research results imply that strategies to improve effective SEWB include increasing physical activity, interaction with nature, art education, a holistic curriculum, and a positive emotional relationship among children, teachers, and parents. SEWB is closely related to mental health, which affects social abilities, academic achievement, and the formation of positive emotions and children's character. In conclusion, this literature review confirms that various efforts to improve children's social-emotional well-being, such as physical activity, engagement with nature, art education, a holistic curriculum, and positive emotional relationships with parents and teachers, have been shown to have a significant impact on children's development. These strategies not only strengthen social and emotional abilities but also improve learning readiness, academic achievement, and long-term psychological well-being. Thus, Social-Emotional Well-Being in children is an essential foundation for optimal growth and development and for future success.